2019
DOI: 10.1088/1361-6560/ab4d8c
|View full text |Cite
|
Sign up to set email alerts
|

CBCT correction using a cycle-consistent generative adversarial network and unpaired training to enable photon and proton dose calculation

Abstract: In presence of inter-fractional anatomical changes, clinical benefits are anticipated from image-guided adaptive radiotherapy. Nowadays, cone-beam CT (CBCT) imaging is mostly utilized during pre-treatment imaging for position verification. Due to various artifacts, image quality is typically not sufficient for photon or proton dose calculation, thus demanding accurate CBCT correction, as potentially provided by deep learning techniques. This work aimed at investigating the feasibility of utilizing a cycle-cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
124
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(135 citation statements)
references
References 43 publications
(28 reference statements)
7
124
0
Order By: Relevance
“…Studies using DL for pCT generation from CBCT are scarce for brain, 55 H&N, [13][14][15] pancreas, 38 or prostate cancer. [35][36][37]55,56 The studies involved an imaging analysis (pCT vs. reference CT), but only half of them evaluated the dose accuracy. Among the three H&N studies using DL for pCT generation from CBCT, [13][14][15] one involved training a U-Net neural network on 50 coregistered CBCT/CT images and performing a test based on data from 10 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using DL for pCT generation from CBCT are scarce for brain, 55 H&N, [13][14][15] pancreas, 38 or prostate cancer. [35][36][37]55,56 The studies involved an imaging analysis (pCT vs. reference CT), but only half of them evaluated the dose accuracy. Among the three H&N studies using DL for pCT generation from CBCT, [13][14][15] one involved training a U-Net neural network on 50 coregistered CBCT/CT images and performing a test based on data from 10 patients.…”
Section: Discussionmentioning
confidence: 99%
“…32 Some studies have recently proposed DLMs for pCT generation from CBCT, mainly for scatter correction. 33,34 Other studies proposed the DLM for pCT generation from CBCT in prostate, [35][36][37] pancreas, 38 and H&N, [13][14][15] for dose calculation. H&N studies have been performed using either U-Net or cycleGAN architectures to generate pCT from CBCT.…”
Section: Introductionmentioning
confidence: 99%
“…The calculation of MAE and GD loss is introduced in our previous studies. 35,40 MI is a measure of mutual dependency between two probability distributions…”
Section: C Cycle-gan For Rsp Image Generationmentioning
confidence: 99%
“…33,34 Kurz et al recently published a deep-learning-based CBCT correction method, which they validated on photon and proton treatments for prostate cancer. 35 The goal of these studies has been to synthesize a CT image that can be used for treatment planning based on the patient's current setup on the treatment table. In this work, we propose to extend a cycle-consistent generative adversarial network (cycle-GAN) from learning a CBCT-to-CT image transformation 36 to learning a CBCT-to-RSP map transformation.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, the most practical and common approach is deformable image registration to map planning CT HU to the (daily) treatment image. Recently, it has been shown that CNNs (DL) provide promising methods for synthetic CT generation based on CBCT or MRI images [86,[94][95][96][97][98][99].…”
Section: Synthetic Ctmentioning
confidence: 99%